بعض المشكلات الاجتماعية وعلاقتها بجودة الحياه لدي الأشخاص ذوي الإعاقة الحركية في مدينة الخمس: جودة الحياة لدى المعاقين (Journal of Academic Research, 2026)
Aim of the Study: This study aimed to identify the nature of social problems faced by individuals with physical disabilities in the city of Al-Khums and their relationship with the level of their quality of life. The study utilized a descriptive-analytical approach and was applied to a sample of (50) individuals with physical disabilities.Key Findings: The study revealed that persons with disabilities face a moderate level of social problems, with economic problems ranking first, followed by family and then health-related issues. It also found a moderate level of quality of life, with a negative impact of social problems on the overall quality of life. Furthermore, the results showed that household income is the most influential variable, as higher income contributes to improving the quality of life. Conversely, no statistically significant differences were found due to variables such as gender, family size, or educational level